O regionalności siedemnastowiecznych kazań pogrzebowych. Część 1: druki lubelskie - Pihan-Kijasowa, Alicja (Wydawnictwo „Poznańskie Studia Polonistyczne” i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
In the 17th century, funeral sermons were a frequent type of public address. Over six hundred of such sermons were published in Poland at the time. They were published by presses all around Poland, so that each region is represented in the production. Consequently, funeral sermons are a good source for research in regional varieties of Polish in the 17th century. The article presents the problem on the example of printed material from Lublin, published in the press owned by Paweł Konrad, Anna Konradowa, and Jan Wieczorkowicz. The inspection of the texts has shown that they represent typical qualities of 17th-century standard Polish, as well as regional differential and frequency-based qualities. Because sermons were written not only by authors from Małopolska, it can be assumed that their language was largely influenced by editors and printers.
On Regional Qualities of 17th-Century Funeral Sermons. Part One: Lublin Prints
Keywords: funeral sermons; regional variety; Lublin printing presses